HUBUNGAN ANTARA KONTROL DIRI DAN HARGA DIRI DENGAN PERILAKU KONSUMTIF TERHADAP GADGET PADA SISWA KELAS XII SMAN 8 BOGOR - Nofitriani, Nisrina Nibras (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
This research is a quantitative study that discusses self-control and self-esteem with consumptive policies on gadgets. The subjects in this study were class 12th grade students at state high school 8 Bogor, with a total of 175 samples using Simple Random Sampling technique. This study uses 3 scale measuring instruments, namely: consumer measuring scale, self-measuring scale and self-esteem measurement scale. Data analysis using bivariate showed a positive relationship between self-control and consumptive relationships with r = 0.175 <0.05. There is a positive relationship between self-esteem and consumptive academic education r = 0.156 <0.05. Based on a multivariate regression test that showed a significant relationship between self-control and self-esteem with a consumptive relationship with R = 0.176 <0.05 and related to the R Square determination coefficient of 0.031.